POTENSI PERMUKIMAN PERAJIN PERAK TRADISIONAL BERBASIS ARSITEKTUR DAN EKONOMI KREATIF DI DESA CELUK, GIANYAR - Ni Putu Ratih Pradnyaswari Anasta Putri; Anak Agung Gede Raka Gunawarman; Ni Luh Anik Puspa Ningsih (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2020)
The silver handicraft industry in Celuk Village, Gianyar is the second largest silver craft center in Indonesia after the Gede city of Yogyakarta. The superiority of silver handicrafts in Celuk village is the unique jewelry design and still going through the traditional craftsmanship process as well as being a tourist destination. In addition, the situation around Celuk Village is seen experiencing rapid development in terms of tourist destinations. The existence of these destinations has the opportunity to optimize the traditional silver crafters' settlements as tourist accommodation. There is a need for research on criteria for tourism accommodation standards, policies, and future governance to be the outcome of this research. The draft academic manuscript which can be a reference for issuing standardization and rules of custom or service is expected to encourage Celuk Village to be the best tourist destination in Gianyar Regency that is independent and able to meet the welfare of its village residents through the existing tourism potential. By using explorative qualitative research methods, found the potential of silver crafters settlements in the village of Celuk where in addition to the space to live and work, there are areas that can be used as guest houses or homestays. Keywords: settlement; tourism; potential